Menopausal hormone therapy: transdermal route of administration - Bińkowska, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Menopausal hormone therapy (MHT) has confirmed effectiveness in the management of both the vasomotor symptoms (hot flushes and sweating) and their indirect consequences (irritability, nervousness, insomnia, memory and concentration problems) and urogenital atrophy symptoms, which are present in most women in perimenopause and postmenopause as a result of estradiol deficiency. The prevention of osteoporosis and reduction of fractures were also proved. Re-analysis of the WHI demonstrated the differences between estrogen and estrogen plus progestin therapy, the effect of age and the time of initiation of the treatment in proximity to menopause on the individual ratio of benefits and risks of MHT. In addition, observational data called our attention to the benefits of the transdermal route of estradiol administration. Avoidance of metabolic and haemostatic effects of the first-pass metabolism in the liver seems to increase the safety of MHT, first of all in aspects of no increased risk of venous thromboembolic complications.